Electronic Structure and Magnetic Coupling of Pure and Mg-Doped KCuF3 - Fausto Cargnoni; Simone Cenedese; Paolo Ghigna; Mario Italo Trioni; Marco Scavini (Advances in Condensed Matter Physics)
We investigated the electronic and magnetic properties of KCuF3 and KCu0.875Mg0.125F3 crystals by means of Density Functional periodic computations at the B3LYP level of theory. We considered four possible magnetic ordering of the unpaired electrons on copper ions. Both materials are correctly predicted as being 1D antiferromagnetic insulators, and the superexchange parameters in the crystallographic ab planes and along the c direction measure +10 and -600 K, respectively. Residual spin polarization is found also on fluorine atoms, in agreement with literature results. We found a complete orbital ordering at Cu sites: in the copper reference frame dxy, dyz, dxz, and dz2 orbitals contain about 2 electrons each, while the dx2-y2 orbital is only partially filled. The perturbation induced by doping of KCuF3 with Mg is very strong and localized on the first shell of F neighbours. Mg has a very small influence on the ordering of the 3d orbitals of copper and on the Cu-Cu magnetic superexchange parameters but reduces significantly the absolute energy differences between the antiferromagnetic ground state and the ferromagnetic phase, in agreement with the experiment. The absence of long range effects makes Mg a suitable dopant for the investigation of strongly correlated electronic systems by means of orbital dilution.